2018
DOI: 10.24843/bulvet.2018.v10.i01.p11
|View full text |Cite
|
Sign up to set email alerts
|

Prevalensi Dan Intensitas Infeksi Trypanosoma Evansi Pada Kuda Di Desa Kabaru, Kecamatan Rindi, Kabupaten Sumba Timur

Abstract: Penyakit Surra merupakan penyakit parasit yang disebabkan oleh Trypanosoma evansi. Kejadian trypanosomiasis dipengaruhi oleh berbagai faktor, yaitu kondisi geografis, keberadaan vektor, cara pemeliharaan dan kondisi fisologis hewan. Penelitian ini bertujuan untuk mengetahui prevalensi dan intensitas infeksi T. evansi pada kuda di Desa Kabaru, Kecamatan Rindi. Sampel yang digunakan berupa darah dari 100 ekor kuda yang diambil dari Desa Kabaru. Pengambilan darah dilakukan melalui vena jugularis dan dibuat prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 2 publications
0
2
2
Order By: Relevance
“…is is lower than the nding of Ndiha et al, (2018) which found between 13 to 71 parasites per 10 elds of view with an average number of 34.5 ± 22.7. e variation of infection may be linked to the condition of the sampled horses where some horses only show general clinical signs of weakness, lethargy, weight loss and some show clinical signs in the form of abdominal oedema.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…is is lower than the nding of Ndiha et al, (2018) which found between 13 to 71 parasites per 10 elds of view with an average number of 34.5 ± 22.7. e variation of infection may be linked to the condition of the sampled horses where some horses only show general clinical signs of weakness, lethargy, weight loss and some show clinical signs in the form of abdominal oedema.…”
Section: Discussioncontrasting
confidence: 64%
“…e stain was cleaned, and the slide was washed with e occurrence of T. evansi in Sumba horses in East Sumba Regency was 20%, which was higher than the previous ndings. Praing et al, (2023) reported a prevalence of only 2.10% in horses in East Sumba Regency, while Ndiha et al, (2018), reported that trypanosomiasis in horses in East Sumba was 8%. Mursalim et al, (2017) stated that T. evansi infection in horses at the Kelara District Slaughterhouse, Jeneponto Regency, South Sulawesi Province was 3.07 % and research by Nur (2017), which was carried out from June to July 2016 on horses in Wajo District, South Sulawesi, amounted to 2.4%.…”
Section: Methodsmentioning
confidence: 99%
“…The diagnosis of T. evansi was made using parasitological techniques that are regarded as simple, quick, and affordable. However, they are insufficient to identify all trypanosome-infected animals, particularly when parasitemia is low and in the chronic form of the disease .The prevalence of T. evansi by microscopic examination in this study is lower than the report of Ndiha et al [21] in horses in Kabaru sub-district, East Sumba district, which is 8% positive by GSBS. The similar result showed with study T.evansi in Sumba island conducted by Nurcahyo et al [22], which found negative result 0.0% in 211 samples of blood smears examined using Giemsa staining.…”
Section: Figure 2 Percentage Catt/tevansi and Pcr Positive For T Evan...contrasting
confidence: 73%
“…First Surra outbreak occurred in 2010 attacking horses and the second outbreak was in 2011 attacking buffaloes. It generated a major problem both in economic and social aspects (Ndiha et al 2018). Due to the extensive traditional management system, the farmers did not realize if the number of their livestock decreased because of Surra.…”
Section: Resultsmentioning
confidence: 99%